Response Surface Methodology Optimization on Ultrasonic‐Assisted Extraction of Chicory (Cichorium intybus L.) and Their UPLC‐ESI‐QTOF‐MS Analysis, Antioxidant and Hepatoprotective Activity - Aizhamal Baiseitova; Ulpan Amzeyeva; Aiya Tolepbergen; Yasmina Ulfanova; Yergazy Shybyray; Lixia Dai; Xiaofei Shang; Abdul Bari Shah; Jeong Yoon Kim; Janar Jenis (eFood)
ABSTRACT Chicory (Cichorium intybus L.) roots are commonly roasted and ground to produce a coffee alternative, valued for its robust, nutty taste and absence of caffeine. Historically, it has been utilized to facilitate digestion, serve as a diuretic, and promote liver function. This study employed a response surface methodology (RSM) for optimization the ultrasonic‐assisted extraction of antioxidant composition from chicory. The optimal extraction conditions (temperature 60°C, extraction duration 4 h, and solid‐to‐solvent ratio of 1:20 g/mL) resulted in the maximum yield and antioxidant capacity. The metabolic content of chicory extract, prepared under optimal conditions, was found by UPLC‐ESI‐QTOF/MS, including aesculetin, caftaric acid, caffeoylmalic acid, scopoletin, and chicoric acid. Moreover, chicory extracts derived under identical conditions in two distinct solvents (96% and 50% ethanol) demonstrated vitality and hepatoprotective action in HL‐7702 cells. This study may offer a perspective for acquiring potential extracts of chicory as a functional food.